Revolutionizing Nigeria's Construction Sector: A Resilient Circular Economy Framework for Sustainable Urban Development - Unegbu, Hyginus (Journal of Sustainable Infrastructure, 2025)
The adoption of circular economy (CE) practices is essential for fostering sustainability in the construction sector, particularly in developing economies like Nigeria. This study investigates the barriers, opportunities, and strategies for advancing CE adoption in Nigeria’s construction industry. Using a mixed-methods approach, data were collected through surveys of 285 construction firms, semi-structured interviews with 40 stakeholders, and system dynamics modeling to evaluate policy scenarios. The findings reveal a low adoption rate of CE principles (18%), with large firms (42%) significantly outpacing SMEs (9%). Urban areas showed higher adoption rates (26%) compared to rural regions (12%), attributed to better access to infrastructure, market-driven incentives, and regulatory enforcement. Key barriers include high financial costs, regulatory gaps, and limited access to advanced technologies such as Building Information Modeling (BIM). Opportunities for accelerating CE adoption were identified, including public-private partnerships (PPPs) to bridge financial and technical gaps, increasing demand for sustainable practices from multinational clients, and integrating CE principles into educational curricula to address skill shortages. System dynamics modeling demonstrated that high policy interventions—combining financial incentives, regulatory reforms, and capacity-building initiatives—could achieve a 60% reduction in construction waste and a 40% improvement in resource efficiency by 2035. This study underscores the need for comprehensive policies, collaborative initiatives, and educational reforms to enable Nigeria’s transition to a sustainable construction sector. By aligning national strategies with global sustainability goals, particularly the United Nations Sustainable Development Goals (SDGs), Nigeria can position itself as a regional leader in sustainable construction.